Psoriasis, Psoriatic Arthritis, and Thyroid Autoimmunity - Ruffilli, Ilaria; Ragusa, Francesca; Benvenga, Salvatore; Vita, Roberto; Antonelli, Alessandro; Fallahi, Poupak; Ferrari, Silvia Martina (Frontiers in Endocrinology, 2017)
Psoriasis (PsO) is a chronic relapsing/remitting autoimmune skin disease, associated with an increased risk of other autoimmune disorders. Psoriatic arthritis (PsA) is a chronic inflammatory arthritis occurring approximately in 30% of PsO patients. Sporadic cases of association between PsO and autoimmune thyroid disorders (AITD) have been reported. However two different recent studies did not find any association between them. In patients with PsO and PsA, an association with AITD has been shown by most of the studies in adults, but not in the juvenile form. In PsA women and men, thyroid autoimmunity [positive antithyroid peroxidase (AbTPO) antibodies, hypoechoic thyroid pattern] and subclinical hypothyroidism were more prevalent than in the general population. An association has been shown also in patients with PsO, arthritis and inflammatory bowel disease, who have more frequently AITD. A Th1 immune predominance has been shown in early PsO, and PsA, with high serum CXCL10 (Th1 prototype chemokine), overall in the presence of AT. This Th1 immune predominance might be the immuno-pathogenetic base of the association of these disorders. A raised incidence of new cases of hypothyroidism, thyroid dysfunction, positive AbTPO, and appearance of a hypoechoic thyroid pattern in PsA patients, especially in women, has been shown recently, suggesting to evaluate AbTPO levels, thyroid function and thyroid ultrasound, especially in PsA women. Thyroid function follow-up and suitable treatments should be performed regularly in PsA female patients at high risk [thyroid-stimulating hormone (TSH) within the normal range but at the higher limit, positive AbTPO, hypoechoic and small thyroid].